The Influence of Titania Nanoparticles on the Electrodeposition of Ni-Mo-W Composites in Aqueous Electrolytes at Different Electrolyte Temperatures - Izagirre‐Etxeberria, Usoa; Podlaha, Elizabeth J. (Frontiers in Chemistry, 2022)
The electrodeposition of Ni-Mo-W alloys and composites with TiO2 are examined with a rotating Hull cell to better understand the influence of the particle on the deposition composition and morphology. The addition of the TiO2 particle to the electrolyte and deposit, significantly affected the deposit composition when the electrolyte temperature was 65 0C. Both Ni and Mo composition in the deposit was enhanced, but not due to a higher reaction rates. The enhancement was a result of an apparent inhibition by the hydrogen evolving side reaction. The W partial current density was most significantly inhibited. The deposit morphology changed with the addition of TiO2 with a reduction of microcracks compared to the particle-free deposit. The results suggest that the adsorption of the hydrogen intermediate from the side reaction is influenced by the particle, hindering hydrogen desorption, and indirectly affects the partial current densities of the nickel, molybdate and tungstate ion reduction and the morphology.